Spatio-Temporal Evolution of Water Consumption and Water Utilization Structure in Pearl River District - XUE Jiao; LIU Xiyan; XU Zheng; HAN Yaxin (Renmin Zhujiang)
Research on spatio-temporal evolution characteristics of water consumption and water utilization structure is significant to integrated management and optimal allocation of water resources. Based on the water consumption data from 1980 to 2019, the spatio-temporal evolution characteristics of water consumption and water utilization structure in Pearl River District were studied by introducing the information entropy and gravity center models. The results show that the water consumption in the Pearl River District increases first and then decreases slightly. The gravity center of water consumption moves first to the east and then to the west. The agricultural water consumption is greatly reduced, and the gravity center moves to the west. Water consumption of other parts increases overall, and the gravity centers move to the east. These variations are consistent with the economic and social development in the Pearl River District. The variations of water utilization structure in the Pearl River District can be divided into two stages, before 2010 and after 2010. In the first stage, the information entropy and equilibrium of water utilization structure increase significantly. The information entropy gravity center of the water utilization structure moves eastward gradually. The variation of water utilization structure in the eastern region is greater than that in the western region. In the second stage, the information entropy and equilibrium of the water utilization structure tend to be stable. The information entropy gravity center of the water utilization structure moves to the west slightly. The water utilization structure is stable. The change in water utilization structure in the western region is larger than that in the eastern region. In terms of population, GDP, industrial added value, and actual irrigated area of farmland, population and actual irrigated area of farmland are the main driving factors for water consumption and water utilization structure changes. The results are helpful to overall understand the variations of water consumption and water utilization structure in the Pearl River District in the past 40 years, which can provide technological support for integrated management and optimal allocation of water resources.